INTRODUCTION TO Computer and Network Security : NAVIGATING SHADES OF GRAY - Brooks, Richard R. (CRC Press, Taylor & Francis Group, 2014)
"This text provides a classroom-tested, practical introduction to software design and implementation, cryptographic tools, and networking issues while addressing social, economic, and political implications. It covers cutting-edge topics, such as wireless security and attacks on websites, privacy and digital rights management, and recent work on security and economics. The text includes hands-on projects to help students better understand how computers and networks function. It also contains a number of case studies and discussion points"--